The public sphere an introduction - McKee, Alan (Cambridge University Press, 2004)
What is happening to public debate in Western cultures? Is our public sphere disintegrating? In the face of popular tabloid newspapers, new forms of reality television and an increasing lack of respect for traditional authorities, many critics are concerned that our society no longer has a rational, informed and unified space where everyone can communicate about the issues that affect us all. In this book Alan McKee answers these questions by providing an introduction to the concept of the public sphere, the history of the term and the philosophical arguments about its function. By drawing on many examples from contemporary mediated culture, McKee looks at how we communicate with each other in public - and how we decide whether changing forms of communication are a good thing for the 'public sphere'